1988
DOI: 10.7326/0003-4819-108-4-524
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Contractility Varies Directly with Blood Ionized Calcium

Abstract: Variations in Ca2+ are directly correlated with clinically significant changes in myocardial contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(62 citation statements)
references
References 28 publications
4
55
0
3
Order By: Relevance
“…In six of eight patients, Ca was measured again approximately 2 hours after completion of each of the dialysis runs; there were no significant differences between the values obtained immediately after dialysis and those measured 2 hours later. 21 Arterial blood gases, electrolytes, creatinine, BUN, magnesium, and hematocrit, as well as body weight and heart rate did not differ among the three studies in each patient. Parathyroid hormone levels were markedly elevated in all but one patient (10.9±3.2 ng/ml, range 1.1-27.5 ng/ml; normal, <1.2 ng/ml).…”
Section: Biochemical Changesmentioning
confidence: 78%
See 1 more Smart Citation
“…In six of eight patients, Ca was measured again approximately 2 hours after completion of each of the dialysis runs; there were no significant differences between the values obtained immediately after dialysis and those measured 2 hours later. 21 Arterial blood gases, electrolytes, creatinine, BUN, magnesium, and hematocrit, as well as body weight and heart rate did not differ among the three studies in each patient. Parathyroid hormone levels were markedly elevated in all but one patient (10.9±3.2 ng/ml, range 1.1-27.5 ng/ml; normal, <1.2 ng/ml).…”
Section: Biochemical Changesmentioning
confidence: 78%
“…Finally, it is possible that the peripheral vasculature in our patients was intrinsically abnormal and thus unable to undergo vasodilation in response to increased pressure and flow. Since total vascular resistance was at most only mildly elevated in our study population, and since we have previously shown that peripheral vasodilation can be easily obtained with nitroprusside in these patients, 21 this explanation seems unlikely. Several methodological issues should be addressed regarding the current study.…”
Section: Hemodynamic Changesmentioning
confidence: 79%
“…Sin embargo, para complementar esta premisa, se realizaron experimentos en los que se evaluó la concentración de calcio intracelular por la administración de derivado carbamacepina-alquino en forma dependiente de la dosis, en ausencia y en presencia de nifedipino. Los resultados señalan que los niveles de calcio intracelular disminuyeron en presencia de nifedipino, lo que vuelve a corroborar que el efecto inducido por el derivado carbamacepina-alquino afecta indirectamente la concentración de este ión intracelular que está involucrado en cambios de la presión intraventricular, como lo señalan algunos investigadores (45,46).…”
Section: Discussionunclassified
“…First, bicarbonate may cause paradoxical intracellular acidification because of the increased generation of cell-permeant CO 2 by mass action effect on the carbonic acid equilibrium (38). Second, the increase in extracellular pH reduces ionized calcium concentration because of chelation by albumin (39), impairing myocardial contractility (40). Third, alkalinization may reduce tissue oxygen delivery by the Bohr effect on hemoglobin oxygen affinity.…”
Section: What Is the Most Effective Treatment For The Patient?mentioning
confidence: 99%